Twofold Pauson-Khand reaction of acyclic and cyclic diynes with ethylene - Rausch, Bernhard J.; Gleiter, Rolf (Tetrahedron letters, 2001)
The twofold DMSO promoted Pauson-Khand reaction of acyclic heptadiynes 1–3, acyclic functionalized nonadiynediol derivatives 7–9 and cyclic diynes 13–15 with ethylene is reported.
Gesehen am 13.11.2020